2004
DOI: 10.1097/00006676-200403000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Spleen-Preserving Total Pancreatectomy With Conservation of the Spleen Vessels:

Abstract: Conventional distal pancreatectomy (cDP) and total pancreatectomy (cTP) also involve removal of the spleen. The spleen, however, is an important organ in the immunologic defense of the host and is worthy of preservation if this can be safely achieved. We performed a spleen-preserving total pancreatectomy (SPTP), with good results, in a Caucasian woman, 66-year-old, affected by pancreatic metastases of renal clear cell carcinoma. This is the first report of a SPTP for pancreatic metastases to our knowledge, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A total of 30 case reports written in English, describing 50 patients, were identified 12367891011121314151617. Patient demographics and presentations are listed in Table 1.…”
Section: Casementioning
confidence: 99%
“…A total of 30 case reports written in English, describing 50 patients, were identified 12367891011121314151617. Patient demographics and presentations are listed in Table 1.…”
Section: Casementioning
confidence: 99%
“…Several authors have described spleen-preserving distal pancreatectomy in order to reduce the changes and risks associated with splenectomy. [1][2][3][4] Complications following splenectomy include leukocytosis, thrombocytosis, overwhelming postsplenectomy sepsis, and some degree of immunodeficiency. There are few reports of spleen-preserving distal pancreatectomy: in the setting of pancreatic trauma, chronic or acute pancreatitis and for benign pancreatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several authors [12-15], suggested spleen preserving distal pancreatectomy in order to reduce postoperative septic complications[16]. The technique of spleen preserving distal pancreatectomy and its absolute and relative contraindications have been described elsewhere [3,13,17,18]. Few retrospective studies have analyzed the influence of splenectomy in the postoperative course after distal pancreatectomy, while one study has analyzed this relationship after total pancreatectomy [3,19,20].…”
Section: Introductionmentioning
confidence: 99%